The Effect of Employee Value Proposition (EVP) and Positive Well-being on Indonesian Retail Company Employees’ Intention to Stay: Moderating Role of Psychological Contract and Social Identity - Yohanes Andy LAIYAN; Rhian INDRADEWA (International Journal of Environmental, Sustainability, and Social Science, 2023)
This paper attempts to examine the effect of employee value proposition (EVP) and positive well-being on employees’ intention to stay in an Indonesian retail company, with psychological contract and social identity serving as the moderating variable. The data were garnered from 330 respondents using a questionnaire, observation, and literature study. This quantitative study applied Partial Least Square (PLS) regression to analyze the data. The result showed that employee value proposition and positive well-being significantly affect employees’ intention to stay at the company. Psychological contract and social identity were found to positively affect the relationship between EVP and employees’ intention to stay at the company.